HUMANISTIC ANIMATION AND ECOLOGICAL LITERACY: ENHANCING READING MOTIVATION AMONG ELEMENTARY STUDENTS - Yasinta Mahendra; Muhammad Fuad; Dina Maulina; Rangga Firdaus; Irawan Suprapto (Jurnal Gramatika, 2025)
This study explores integrating humanistic animated learning media with ecological education to improve elementary students’ reading interest. Drawing on principles of humanistic pedagogy, the intervention aimed to cultivate empathy, critical thinking, and environmental awareness while simultaneously stimulating literacy skills. A quasi-experimental design was employed with 217 participants, who engaged with animated stories centered on ecological themes. Data were collected using questionnaires, classroom observations, and interviews, and analyzed using descriptive and inferential statistics. The results revealed that students exposed to the animated human-ecological content demonstrated significantly higher reading interest levels than their control group peers. Moreover, the narratives fostered a deeper engagement with ecological issues, highlighting the potential of digital media to address dual objectives of literacy development and value education. However, limitations of the study include the short intervention period, reliance on self-reported measures, and lack of long-term follow-up. These findings contribute to current literacy and environmental education debates by showing that combining humanistic approaches with multimedia can produce meaningful educational outcomes. Future research should extend this model across different cultural and socio-economic contexts, employ longitudinal designs, and assess broader cognitive and affective impacts. This study provides insights for educators, curriculum developers, and policymakers seeking innovative strategies to integrate literacy promotion with sustainable education goals.